Health awareness and life-style practices of foodservice employees - Ladki, Said M. (1998)
Full-time foodservice employees (425) responded to a questionnaire on perceived life-style activities. The majority of respondents seldom missed work, made time for leisure activities, and felt secure in their jobs (p<0.05). The more educated the employee, the greater the perception of being overweight (r = 0.798; p< 0.05). Skilled and technical employees consumed more coffee or colas in comparison to professional employees (p< 0.05). To improve general health, 68% of the respondents expressed interest in participating in nutrition education and stress management classes rather than participating in physical fitness sessions.